1997
DOI: 10.1038/sj.jhh.1000384
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of hypertension in the Indian social class and heart survey

Abstract: To determine the association of socio-economic status 1.05-1.14; women 1.08, 95% CI 1.05-1.13), body mass (SES) and prevalence of hypertension and its risk facindex (odds ratio: men 1.12, 1.08-1.18; women 1.11, tors in a rural population, a cross sectional survey was 1.06-1.16) and sedentary lifestyle (odds ratio: men 1.45, conducted in two randomly selected villages in the 1.32-1.58; women 1.38, 1.26-1.49). Only weak but sigMoradabad district in North India. There were 1935 resinificant associations were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 4 publications
8
26
0
Order By: Relevance
“…24,25 The prevalence of hypertension in Bavi was low compared to national figures in developed countries such as the United States of America, Australia and the United Kingdom, as well as other developing countries such as Thailand, Indonesia and China. 4,[26][27][28] Comparing studies conducted in rural areas in developing countries, the hypertension prevalence found in this study was slightly lower than the one revealed in a rural community of India (17.3% among people aged 25-64 years) 29 but higher than the figures of 15% in a remote rural region of Pakistan 11 and of 10% in rural communities of Iran. 30 This study also revealed an unacceptably high percentage of hypertensives (83%) not being aware of their high blood pressure.…”
Section: Discussionmentioning
confidence: 66%
“…24,25 The prevalence of hypertension in Bavi was low compared to national figures in developed countries such as the United States of America, Australia and the United Kingdom, as well as other developing countries such as Thailand, Indonesia and China. 4,[26][27][28] Comparing studies conducted in rural areas in developing countries, the hypertension prevalence found in this study was slightly lower than the one revealed in a rural community of India (17.3% among people aged 25-64 years) 29 but higher than the figures of 15% in a remote rural region of Pakistan 11 and of 10% in rural communities of Iran. 30 This study also revealed an unacceptably high percentage of hypertensives (83%) not being aware of their high blood pressure.…”
Section: Discussionmentioning
confidence: 66%
“…According to old WHO guidelines, the prevalence of hypertension in rural populations also showed an increase (Table 6). Shah in Mumbai 49 reported a prevalence 18 In south India, Kerala 67 the prevalence was as high as 17.8 ± 1.1% in a suburban village. It seems that there is a significant increase in the prevalence of hypertension in the last few decades in India (Mantel-Haenzel 2 = 5.93, P Ͻ 0.01).…”
Section: Prevalence Of Hypertensionmentioning
confidence: 96%
“…5,[15][16][17][18] Studies from the cities of Ludhiana, 60 Bombay, 55 Jaipur 73 and Moradabad 17 showed a prevalence of more than 10%. Statistical analysis of this trend in comparable surveys showed a significant increase demonstrated by non-parametric analysis (Mantel-Haenzel 2 = 6.11 P Ͻ 0.01).…”
Section: Prevalence Of Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations